Torsion of a Wandering Spleen - Haque, T; Hossain, S; Alam, KABMT; Rahman, MA (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Wandering spleen is a rare clinical condition characterized by ectopic positioning of the spleen due to abnormal peritoneal attachments including the lienorenal and gastrosplenic ligaments. The spleen can wander or migrate into various positions within the abdomen or pelvis due to this ligamentous laxity. The clinical presentation of patients with this entity is variable and can range from an incidental finding to an acute abdomen associated with torsion. Various imaging modalities can be utilized for the diagnosis of this condition .A variable treatment options for torsion of wandering spleen include splenectomy or splenopexy. Here we described a case of 32 years young lady with acute abdomen due to torsion of a wandering spleen. Diagnosis was made on the basis of clinical findings and abdominal ultrasound. Laparotomy was performed and the infarcted spleen was removed. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21008 J Bangladesh Coll Phys Surg 2013; 31: 219-222